The Structural Configuration and Mechanical Performance of a New Cable-Supported Reciprocal Structure - Guang Guo; Wenfeng Du; Chen Wang; Haoran Liu; Nasim Uddin (Buildings)
Reciprocal structures represent a category of spatial structural systems characterized by mutually supporting connections between components, which are primarily employed in roof systems and spatial frameworks. Insufficient stiffness is a critical challenge for the practical application of reciprocal structures in engineering. This study introduces a new cable-supported reciprocal structure, which integrates rigid beams and flexible cables through struts, inspired by the construction principles of beam string structures. By optimizing the force transfer path, the overall performance of the structure is improved. Through finite element analysis, a comprehensive investigation was conducted on the static behavior and parametric analysis of this new reciprocal structure. The research results show that the rational determination of key parameters, including the rise/span ratio, strut height, and cable length, demonstrates significant efficacy in reducing the maximum displacement of this new reciprocal structure under uniformly distributed load. The stiffness of the new cable-supported reciprocal structure increases by 17% compared to that of the general reciprocal structure, while the total steel consumption decreases by 12%. The proposed new cable-supported reciprocal structure presents an innovative and viable configuration within the domain of reciprocal structures.